The Link between Energy Consumption and Economic Growth in Gulf Cooperation Council Countries - Abul, Sadeq J.; Satrovic, Elma; Muslija, Adnan (International Journal of Energy Economics and Policy, 2019)
The purpose of this research article is to provide the fresh evidence on the link between energy consumption (ENE) and economic growth (GDP) while controlling for the impact of CO2 emissions (CO) in the case of GCC (Gulf Cooperation Council) countries. To conduct the empirical study we have employed the panel VAR methodology in the period 1980-2014. The results suggest that economic growth increases the energy consumption. However, the negative link between CO2 emissions and economic growth is reported, implying the great awareness of the GCC countries on the environmental problems connected with the fossil fuels based energy. Thus, there is a serious incentive in these countries to deal with the potential environmental issues. One of the good alternatives is renewable energy. In addition, the increase in the energy efficiency is considered to be an important task in the future. Keywords: economic growth; energy consumption; Gulf Cooperation Council JEL Classifications: O13; O44 DOI: https://doi.org/10.32479/ijeep.7872